KONFLIK SYI’AH-SUNNI PASCA-THE ARAB SPRING - Ahmad Sahide (Jurnal Kawistara, 2013)
Conflict of Syi’i-Sunni is the conflict that has long history. The seed of this conflict began since the deathof Prophet Muhamad SAW. In the beginning, this conflict is the political conflict, it related about whowould be the successor of Muhammad’s leadership after his death. However, this conflict was broughtto the religious (aqidah) conflict among the followers of Ali and the followers od Abu Bakar and theother Friends. This conflict has big impact in colouring the history of the Islamic world civilizationwhich is so difficult to be compromised, to the present. Even this conflict participates in colouring thepolitical conflict in the Middle East, mainly the Arab World, since the Arab Spring exploded in the earlyof 2011 last. The Arab Spring doesn’t just make popular the word of democracy in the political discourseof the Middle East, but also the sentiment of Syi’i-Sunni makes hot the political atmosfer. This writingtries to read the history and the development of Syi’i-Sunni conflict in the Middle East contemporerly.